An in vitro study to elucidate the effects of Product Nkabinde on immune response in peripheral blood mononuclear cells of healthy donors - Setlhare, Boitumelo; Letsoalo, Marothi; Nkabinde, Siphathimandla Authority; Nkabinde, Magugu; Mzobe, Gugulethu; Mtshali, Andile; Parveen, Sobia; Ngcobo, Samukelisiwe; Invernizzi, Luke; Maharaj, Vinesh; Ngcobo, Mlungisi; Gqaleni, Nceba (Frontiers in Pharmacology, 2024)
A significant number of the South African population still rely on traditional medicines (TM) as their primary healthcare due to their belief in their holistic healing and immune-boosting properties. However, little to no scientific data is available on the effects of most TM products on cytokine and cellular biomarkers of the immune response. Here, we evaluated the impact of traditional medicine [Product Nkabinde (PN)] in inducing cellular and cytokine biomarkers of inflammation in peripheral blood mononuclear cells (PBMCs) from eight healthy volunteers.PN was supplied by a local Traditional Health Practitioner (THP). The IC50 (half maximum concentration) of the standardized extract on isolated PBMCs was established using the cell viability assay over 24 h of incubation. Luminex and flow cytometry assays were used to measure cytokine and cellular levels in PBMCs stimulated with PN and/or PHA over 24, 48, and 72 h, respectively.The IC50 concentration of PN in treated PBMCs was established at 325.3 µg/ml. In the cellular activation assay, the percentages of CD38-HLA-DR+ on total CD4+ T cells were significantly increased in PBMCs stimulated with PN compared to unstimulated controls after 24 h (p=0.008). PN significantly induced the production of anti-inflammatory IL-10 (p=0.041); proinflammatory cytokines IL-1α (p=0.003), TNF-α (p<0.0001); and chemokine MIP-1β (p=0.046) compared to the unstimulated control after 24 h. At 48 h incubation, the production of proinflammatory cytokines IL-1α (p=0.034) and TNF-α (p=0.011) were significantly induced following treatment with PN.We conclude that the PN possesses in vitro immunomodulatory properties that may influence immune and inflammatory responses. More studies using PN are needed to further understand key parameters mediating induction, expression, and regulation of the immune response in the context of pathogen-associated infections.